2021
DOI: 10.1084/jem.20201831
|View full text |Cite
|
Sign up to set email alerts
|

Large pH oscillations promote host defense against human airways infection

Abstract: The airway mucosal microenvironment is crucial for host defense against inhaled pathogens but remains poorly understood. We report here that the airway surface normally undergoes surprisingly large excursions in pH during breathing that can reach pH 9.0 during inhalation, making it the most alkaline fluid in the body. Transient alkalinization requires luminal bicarbonate and membrane-bound carbonic anhydrase 12 (CA12) and is antimicrobial. Luminal bicarbonate concentration and CA12 expression are both reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
22
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 45 publications
0
22
0
Order By: Relevance
“…For this mechanism to be functional, the tissue must be able to accommodate rapid CO 2 hydration and dehydration reactions at rates that are relevant to the respiratory cycle. These reactions are catalyzed by carbonic anhydrase, which the authors showed to be tethered to the epithelial surface (Kim et al, 2021). Inhibitors of carbonic anhydrase greatly dampened the rate of alkalinization of artificial ASL upon reduction of CO 2 abundance.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…For this mechanism to be functional, the tissue must be able to accommodate rapid CO 2 hydration and dehydration reactions at rates that are relevant to the respiratory cycle. These reactions are catalyzed by carbonic anhydrase, which the authors showed to be tethered to the epithelial surface (Kim et al, 2021). Inhibitors of carbonic anhydrase greatly dampened the rate of alkalinization of artificial ASL upon reduction of CO 2 abundance.…”
mentioning
confidence: 99%
“…In a highly mechanistic study reported here (Kim et al, 2021), an investigative team led by Dr. John Hanrahan (McGill University) has explored an important physiological function not previously considered but likely to be relevant to CF and a variety of other pulmonary diseases: respiratory cycling of airway surface pH, which contributes to host defense mechanisms.…”
mentioning
confidence: 99%
See 3 more Smart Citations